Growing roots: the role of collective community gardening in cultural food insecurity and social integration of African immigrants in Alberta, Canada - Destiny Otoadese; Issa Kamara; Elizabeth Onyango (BMC Public Health)
Abstract Background In western countries such as Canada, immigrants are experiencing cultural food insecurity - that is the inability to acquire, afford, and access one' ethnic foods and community gardens have emerged as potential area for addressing cultural food insecurity. However, limited knowledge exists on the role of collective community gardens in addressing the cultural food needs of immigrant communities. Methods We conducted a community-based participatory research (CBPR) informed by an Afrocentric lens using quantitative and qualitative research methodologies. Data collection involved an online survey (n = 119) which was co-developed and co-administered with our community partners– Sinkunia Community Development Organization (SCDO). Semi-structured, in-depth interviews (IDI) were also conducted with purposefully sampled participants (n = 10) to obtain nuanced narratives. This study included Black identifying African immigrants from sub-Saharan countries. Results High prevalence of food insecurity (75.6%) was observed in the survey participants, higher than the general Canadian household prevalence rate. Participants recalled experiencing food insecurity ranging from mild (39.5%) to moderate (26.1%) and severe (10.1%) food insecurity. High prevalence of cultural food insecurity (80.7%) was also observed with most participants reporting some level of deprivation of cultural foods. However, participants demonstrated resilience and adaptability in maintaining their cultural food-ways amid these challenges. Collective community gardens allowed immigrant communities to: (a) cultivate connections through food production (‘seeds of sovereignty’); (b) build intergenerational bridges (‘seeds of identity’); (c) grow together across generations; and (d) grow strong to embody health and wellbeing. Conclusion The findings contribute to a growing body of evidence on the embodied benefits of community gardens for food security and social place-making of immigrant populations. High interest and engagement in gardening activities in the population suggests potential for expansion of community-led initiatives to support social and cultural integration of immigrant. This is important to Alberta’s and to Canada’s current and future sustainable economic and social growth.